2003
DOI: 10.1074/jbc.m306904200
|View full text |Cite
|
Sign up to set email alerts
|

Direct Activation of Phospholipase C-ϵ by Rho

Abstract: Unique among the phospholipase C isozymes, the recently identified phospholipase C-⑀ (PLC- Comparative sequence analysis of mammalian phospholipase C isozymes revealed a unique ϳ65 amino acid insert within the catalytic core of PLC-⑀ not present in PLC-␤, ␥, ␦, or . A PLC-⑀ construct lacking this region was no longer activated by Rho or G␣ 12/13 but retained regulation by G␤␥ and H-Ras. GTP-dependent interaction of Rho with PLC-⑀ was illustrated in pull-down experiments with GST-Rho, and this interaction was r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
112
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(118 citation statements)
references
References 38 publications
5
112
0
1
Order By: Relevance
“…4A). Treatment with C3 significantly impaired production of InsPs in response to thrombin (68 Ϯ 13% inhibition), which is consistent with evidence that RhoA binds to and can directly activate PLC (13). In contrast, the InsP response to S1P and LPA was unaffected by C3 pretreatment (Fig.…”
supporting
confidence: 86%
See 1 more Smart Citation
“…4A). Treatment with C3 significantly impaired production of InsPs in response to thrombin (68 Ϯ 13% inhibition), which is consistent with evidence that RhoA binds to and can directly activate PLC (13). In contrast, the InsP response to S1P and LPA was unaffected by C3 pretreatment (Fig.…”
supporting
confidence: 86%
“…Studies using heterologous expression demonstrate that, in contrast to PLC␤, PLC is not activated by G␣ q but rather by G␤␥ and G␣ 12 signaling (5, 9). Most remarkably, PLC is activated by direct binding of small GTPases, including Ras, Rap1, and Rap2B (6,7,(10)(11)(12) as well as by RhoA (13). Thus, PLC appears to serve as a nexus for signaling, responding to inputs from a broad range of receptor activation and uniquely linking PLC to small-GTPase pathways (14,15).…”
mentioning
confidence: 99%
“…An increase in substrate hydrolysis by PLCe in transfected cells have been observed after stimulation by diverse stimuli including epidermal growth factor (EGF), lysophosphatic acid (LPA), sphingosine-1-phosphate (S1P), adrenalin and acetycholine (Schmidt et al, 2001;Evellin et al, 2002;Kelley et al, 2004). Furthermore, these and other studies suggest that signaling pathways triggered by these agonists could be quite broad and in some cases independent of Ras family GTP-ases (Lopez et al, 2001;Wing et al, 2001Wing et al, , 2003Kelley et al, 2004). However, regarding that most approaches involved overexpression of PLCe, it still remains to be established which of the possible regulatory interactions are physiologically relevant.…”
Section: Introductionmentioning
confidence: 93%
“…The specific role of RhoA in signaling pathways turned on during T cell activation has not been examined thoroughly, although reports have shown that the GTPase is able to activate the NFAT-binding partner AP-1 [15] as well as NF-κB [16 -18]. In addition, RhoA and its upstream activator Gα13 have been shown to increase the activity of phospholipase Cε (PLCε), leading to increased levels of intracellular calcium [19].…”
Section: Introductionmentioning
confidence: 99%